2021
DOI: 10.3389/fpls.2021.719092
|View full text |Cite
|
Sign up to set email alerts
|

Floral Scents of a Deceptive Plant Are Hyperdiverse and Under Population-Specific Phenotypic Selection

Abstract: Floral scent is a key mediator in plant-pollinator interactions. However, little is known to what extent intraspecific scent variation is shaped by phenotypic selection, with no information yet in deceptive plants. In this study, we collected inflorescence scent and fruit set of the deceptive moth fly-pollinated Arum maculatum L. (Araceae) from six populations north vs. five populations south of the Alps, accumulating to 233 samples in total, and tested for differences in scent, fruit set, and phenotypic selec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 70 publications
2
43
0
Order By: Relevance
“…indole, p‐cresol and 2‐heptanone) were not correlated with species‐specific pollinator attraction. A recent study by Gfrerer et al (2021) also found that variation in the aforementioned foetid‐smelling VOCs were not among those which significantly influenced fruit sets in A. maculatum . Given that blends of indole, p‐cresol and 2‐heptanone are known to be attractive to Psychoda species (Kite et al 1998), these compounds appear to be generally attractive to all species.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…indole, p‐cresol and 2‐heptanone) were not correlated with species‐specific pollinator attraction. A recent study by Gfrerer et al (2021) also found that variation in the aforementioned foetid‐smelling VOCs were not among those which significantly influenced fruit sets in A. maculatum . Given that blends of indole, p‐cresol and 2‐heptanone are known to be attractive to Psychoda species (Kite et al 1998), these compounds appear to be generally attractive to all species.…”
Section: Discussionmentioning
confidence: 89%
“…Arum maculatum inflorescences (Fig. 1) are pollinated deceptively, by emitting complex VOC blends which are known to vary within and among populations in England (Kite 1995, Kite et al 1998, Diaz and Kite 2002, France (Chartier et al 2011(Chartier et al , 2013 and across the Alps (Gfrerer et al 2021). The floral odour of A. maculatum is similar to dung or decomposing organic matter (Lack and Diaz 1991), mimicking the natural brood sites of their main pollinators, the moth flies Psychoda phalaenoides and Psycha grisescens (Diptera: Psychodidae).…”
Section: Introductionmentioning
confidence: 99%
“…Floral visitor abundance was a significant predictor of the presence of an infructescence in both regions, i.e., north ( p = .004, df = 125; performance of the GLM, hereinafter referred to as GLM fit: χ 2 = 9.26, p = .002) and south ( p < .001, df = 131; GLM fit: χ 2 = 19.35, p < .001) of the Alps ( Supplementary Figure S2 ). Fruit set was highly variable ( Figure 4 ) and the mean fruit set among the populations ranged between 1 and 86.1% in both of the regions ( Supplementary Table S2 ; see also Gfrerer et al, 2021 ). When pooled across regions, the overall visitor abundance had a significant effect (slope = 11.06, p = .005) on fruit set (performance of the LM, hereinafter referred to as LM fit: adj.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a putatively high attractiveness of northern A. maculatum to female P. phalaenoides inferred herein could explain why this specific interaction has been repeatedly observed in other northern locations of the plant’s distribution ( Lack and Diaz, 1991 ; Diaz and Kite, 2002 ; Espíndola et al, 2011 ; Chartier et al, 2013 ; Gibernau, 2016 ). The recently reported differences in scent bouquets between A. maculatum populations from north vs. south of the Alps ( Gfrerer et al, 2021 ) might play a key role in the differential attraction of the psychodid moth flies. To test this hypothesis, behavioral assays assessing whether these psychodid species respond differently to northern vs. southern scent bouquets are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation